Green credit and bank performance in Indonesia - Sri Andaiyani; Fida Muthia; Agil Novriansa (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2023)
A new challenge for the banking sector In Indonesia is integrating social aspects in firm performance reports. Green Credit is expected to substantially drive capital allocation to sustainable development which eventually will impact the pattern of production and consumption in the future. In this study, using commercial bank data in Indonesia, we estimate an empirical model of the effect of green credit on bank performance in Indonesia during the period 2015 to 2021. We employ a panel dynamic model using the Generalized Method of Moments (GMM). We differ bank performance twofold which are return on asset (ROA)). The main finding shows that green credit significantly abates bank performance since some green economy projects focus on the public welfare. Therefore, green credit could not result in high returns. The government should formulate a policy of providing incentives to banks that offer green credit. Thus, it could encourage the willingness of banks to lend more funds to the green economy.